Anabasis als Weg zwischen den Künsten: intermediale Bezüge auf Malerei in Manfred Winklers Lyrik - Dácz, Enikő (Naharaim, 2025)
Anabasis shapes Manfred Winkler's lyrical path in many variations, leading him through the fields of other arts and between them. The present article follows this lyrical path, whereby it understands itself as anabasis, a "wandering through uncharted territory", in the sense of Alain Badiou. Winkler's path to poetry implies an encounter that turns into an embrace or entanglement, forcing the creative self to constantly adapt and reminding the reader of Celan's conception of the poem as a dialogue, while recalling image quotations when oscillating between different art fields. Winkler's palette of intermedial references is broad, ranging from Michelangelo and Botticelli to Vincent van Gogh, Marc Chagall, Paul Gauguin, Edvard Munch, and Pablo Picasso. However, less famous artists such as Gyula Zilzer, Hans Fronius or Caspar Neher also belong to the expanded fields of this poetry.